Pharmacological Treatment of Insomnia – Drug Classes, Mechanisms, Risk Factors for Dependence, and Clinical Consequences of Long-Term Therapy - Imbirska, Beata; Prager-Zimny, Marta; Cyrulik, Michalina; Ramlau, Natalia; Kolenda, Dominika; Fischer, Zuzanna; Podolak, Marcin; Hładki, Michał; Simachi, Michalina; Janiszewska, Michalina (Journal of Education, Health and Sport, 2025)
Introduction Insomnia is a widespread sleep disorder impacting quality of life and overall health. While non-pharmacological approaches are effective, pharmacological treatment remains essential, especially in chronic or severe cases. Over time, various sleep-inducing drugs have been developed, targeting different neurochemical pathways. However, prolonged use may lead to tolerance, dependence, cognitive decline, and rebound insomnia. Aim of the Study This review aims to provide an overview of pharmacological treatments for insomnia, emphasizing drug mechanisms, dependence risk factors, and the clinical consequences of long-term therapy. Understanding these elements is vital for optimizing treatment and minimizing harm. Materials and Methods The review is based on literature from PubMed and Google Scholar, using search terms such as “Sleep Disorders Treatment,” “Insomnia,” and “Sleep Drug Dependence.” Conclusion Pharmacotherapy plays a key role in insomnia management when non-drug methods are insufficient. Though effective short-term, these medications pose risks if used long-term. Clinicians must understand the pharmacodynamics and associated risks to guide safe, informed treatment. This review underscores the need for cautious prescribing, routine monitoring, and combining drug therapy with behavioral interventions. Future research should prioritize safer options that retain efficacy while minimizing addiction potential.